Nitrate leaching from soils amended with different organic residues - Carneiro, J.P. (2011)
Leaching of nitrate (NO3-) is a flux economically undesirable, and involves negative consequences to the environment, such as water contamination. Along 2004-2007, about 30% of Portuguese network stations presented a mean nitrate concentration in groundwater >25 mg NO3 L-1. Under similar conditions, NO3--N leaching losses from effluents are generally lower than those from N fertilizers (Di and Cameron, 2002). However, numerous studies have shown that NO3- leaching is a common and sometimes serious problem when organic wastes are used (Sims, 1995). The effect of climate, cropping system used, time of N application and use of a nitrification inhibitor, are some of the factors that, according to Randall and Goss (2001), can affect nitrates in subsurface drainage. The objective of this trial was to evaluate losses of NO3--N by leaching in Mediterranean conditions, when different organic wastes (cattle slurry, sewage sludge and urban waste compost) were used as N sources in a double-cropping system producing oats and maize forage. The use of a nitrification inhibitor (DCD), the splitting application of residues and the use of an organic residue with high C/N ratio (pulp mill sludge) were evaluated as leaching mitigation measures.